UPAYA PENINGKATAN PENDAPATAN RUMAH TANGGA MISKIN PENGRAJIN BATIK DENGAN CANTING ELEKTRIK (Studi Empirik pengarajin Batik di Kecamatan Gunung Pati Semarang) - Rahayuningsih, Sri; Murdiyanto, Agus (Proceeding Fakultas Ekonomi, 2014)
The aim of this research is to know the efforts of woman empowerment in order to raise poor family income.Model of poor woman in based of formation groups of house wifes as batik crafts woman using cantingelectric formulates some points such as : increasing the profile of poor woman activity, the active role ofwoman ini empowerment which can increase poor family income, the earnings of batik crafts woman, thework time of batik crafts women, the effectiveness of using electric canting, success formation of craftswoman groups. To get the research model, method descriptive qualitative analysis are used. The resulthoped is model of district empowerment woman known at Gunung Pati Semarang, the are Jatirejo, Siwarakand Gunung Pati. Based on descriptive of qualitative analysis. The results of this research are 67,35 percentgain big profit after they became the member of batik crafts woman group. The strengths that poor womanhave are availability of time empowerment, also the their persistence to work to get more income.Participation approach is way to empower poor woman. This approach is able to invite housewives toparticipate in increasing self quality. Beside that, this approach is flexible way because there is no standardprocedure. However, it is more adapted with the condition, potential and distribution from poor woman inthat village.Keyword : woman empowerment, poor the household income, source utilization poor household batik craftswoman.